Laser Patterning of Self‐Assembled Monolayers on PEDOT:PSS Films for Controlled Cell Adhesion. Issue 16 (29th June 2017) - Ohayon, David; Pitsalidis, Charalampos; Pappa, Anna‐Maria; Hama, Adel; Zhang, Yi; Gallais, Laurent; Owens, Roisin M.
Abstract : Conducting polymers have shown great potential as a means to interface electronics with living tissues, toward a plethora of different biological applications ranging from in vitro to in vivo systems. However, the development of effective functionalization approaches to render this interface biomimetic still remains rather challenging, due to the lack of inherent surface functionalities in such polymers. Here, a straightforward and versatile modification strategy of poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) surfaces is demonstrated for preferential and spatially confined cell adhesion and growth. By combining three simple surface modification steps, including chemical modification using self‐assembled monolayers and their selective laser ablation, this study is able to design either cell‐adhesive or cell‐repulsive patterns of various shapes on PEDOT:PSS films. Studies using Madin–Darby canine kidney II epithelial cells reveal preferential cell adhesion and growth with good precision following the preformed patterns. The proposed surface modification approach can be extended to encompass a variety of polymeric biomaterials, without affecting their bulk properties. Abstract : A surface modification method to achieve controlled cell adhesion and growth on top of electrically conducting polymer films is presented. Using chemical grafting followed by selective laser ablation, cell‐attracting and cell‐repelling areas are introduced, leading to spatially controlled localization of cell populations. This simple, minimally destructive approach can be applied on a variety of substrates for bioelectronic applications.